Bioinformatic Analysis of Deleterious Non-Synonymous Single Nucleotide Polymorphisms (nsSNPs) in the Coding Regions of Human Prion Protein Gene (PRNP) - Kourosh Bamdad; Fatemeh Rahimi Gharemirshamlu; Sirous Naeimi (Fasa University of Medical Sciences, 2016)
Background & Objective: Single nucleotide polymorphisms are the cause of genetic variation to living organisms. Single nucleotide polymorphisms alter residues in the protein sequence. In this investigation, the relationship between prion protein gene polymorphisms and its relevance to pathogenicity was studied. Material & Method: Amino acid sequence of the main isoform from the human prion protein gene (PRNP) was extracted from UniProt database and evaluated by FoldAmyloid and AmylPred servers. All non-synonymous single nucleotide polymorphisms (nsSNPs) from SNP database (dbSNP) were further analyzed by bioinformatics servers including SIFT, PolyPhen-2, I-Mutant-3.0, PANTHER, SNPs & GO, PHD-SNP, Meta-SNP, and MutPred to determine the most damaging nsSNPs. Results: The results of the first structure analyses by FoldAmyloid and AmylPerd servers implied that regions including 5-15, 174-178, 180-184, 211-217, and 240-252 were the most sensitive parts of the protein sequence to amyloidosis. Screening all nsSNPs of the main protein isoform using bioinformatic servers revealed that substitution of Aspartic acid with Valine at position 178 (ID code: rs11538766) was the most deleterious nsSNP in the protein structure. Conclusion:  Substitution of the Aspartic acid with Valine at position 178 (D178V) was the most pathogenic mutation in the human prion protein gene. Analyses from the MutPred server also showed that beta-sheets' increment in the secondary structure was the main reason behind the molecular mechanism of the prion protein aggregation.